Nobiletin exhibits potent inhibition on tumor necrosis factor alpha‐induced calcification of human aortic valve interstitial cells via targeting ABCG2 and AKR1B1. (23rd April 2019) - Xu, Kang; Huang, Yuming; Zhou, Tingwen; Wang, Chunli; Chi, Qingjia; Shi, Jiawei; Zhu, Peng; Dong, Nianguo
Abstract : Inflammation is considered to be one of the initial critical factors in the occurrence of calcific heart valve disease. This study was to prove Nobiletin (NBT) inhibits inflammation‐caused calcification of human valve interstitial cells (hVICs) and to elucidate the involved molecular mechanisms. Tumor necrosis factor‐alpha (TNF‐α)‐induced hVICs were treated with or without NBT. Cell growth and calcification of hVICs were assessed. RNA sequencing was utilized to investigate the gene expression changes. Molecular target prediction and docking assay were further performed. NBT interfered with hVIC growth under TNF‐α condition in a dose‐dependent manner also presented a gradual decrease of positive Alizarin Red S staining, down‐regulation of BMP2, and RUNX2 gene expression. Based on the global gene expression cluster, control and TNF‐α plus NBT group showed a high similarity versus TNF‐α only group. After Venn interaction of differential expression genes (DEGs), 2, 236 common DEGs were identified to display different biological functions and signaling pathways. ABCG2 and AKR1B1 were further selected as prediction targets of NBT involved in RELA, TNF, BMP2, RUNX2, etc. interactions in mediating hVIC calcification. The results show that NBT is a natural product to prevent the occurrence of heart valve calcification.